COVID-19 AND THE DIGITAL TRANSFORMATION OF EDUCATION: THE CASE OF LATVIA AND LITHUANIA - Trinkūnienė, Sandra; Juskaite, Loreta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Educational ecosystem is facing rapid changes due emerging technologies and their rapid penetration to daily use. When the COVID-19 pandemic emerged, it only accelerated many of these trends. Nevertheless, some education systems have been able to adapt to the changing situation and digital transformation more easily than others. Digital competence is essential for learning, work and active participation in society in digital transformation context. Given the pressure of change on existing learning institutions and learning models, ICT offers broad opportunities for developing a different view. In order for digital education actors to adapt to the digital transformation in the education sector, they also need to have the skills needed to use technology effectively. However, there is a lack of computer and technological literacy. In Latvia and Lithuania, about one in three workers has limited or no digital skills, and most STEM vacancies remain unfilled because workers do not have the necessary competencies and are not inclined to study or retrain. The aim of the study is to assess the effect of dynamic capabilities for added value educational outcomes during COVID-19 recession. The results of the study revealed that dynamic capabilities have a direct positive eﬀect on value based education outcomes.